Recommendations for ultrasound examination in ophthalmology. Part I: Ultrabiomicroscopic examination - Kosmala, Jacek (J Ultrason, 2018)
Range of ultrasounds used in medical imaging is between 2 and 80 MHz. The highest frequencies are applied in medical imaging of an anterior segment of an eyeball. This paper covers the newest method of ultrasound imaging – an ultrabiomicroscopic examination. Its name reflects resolution which has so far been unavailable, and which allows for imaging a structure of the examined tissues. The article includes basic information about the structure and principles of operation of ultrabiomicroscopic examination tools. Moreover, its position among other methods for echographic examination of an eyeball was determined. Examination techniques and the role of standards of conduct at each stage of a diagnostic procedure were discussed. A role of insufficient cooperation between constructors of new ultrasonographic diagnostic tools and software IT specialist with the users of these tools, which results in the lack of consistency between the components of these sets was emphasized. Based on long term experience in ultrabiomicroscopic examinations, the authors shared observations on practical aspects of this method. Finally, indications and contraindications for ultrabiomicroscopic diagnostics were listed. Introduction of an ultrahigh frequency ultrasound probe allowed for the visualization of an post-iridial area of an anterior segment of an eyeball – an area whose diagnosis is impossible with other diagnostic methods. A wide spectrum of diagnostic indications, which covers both diseases and development anomalies of an anterior segment of an eyeball, confirms a special meaning of this method.